The tourist attraction - Morgenthaler, Sarah ([Moose Springs, Alaska], 2020)
"Contemporary Romcom: When Graham Barnett named his diner The Tourist Trap, he meant it as a joke. Now he's stuck slinging reindeer dogs to an endless string of resort visitors who couldn't interest him less. Not even the sweet, enthusiastic tourist in the corner who blushes every time he looks her way... Two weeks in Alaska isn't just the top item on Zoey Caldwell's bucket list. It's the whole bucket. One look at the mountain town of Moose Springs and she's smitten. But when an act of kindness brings Zoey into Graham's world, she may just find there's more to the man than meets the eye...and more to love in Moose Springs than just the Alaskan wilderness"--